Cytogenetics studies in Brazilian species of Pseudophyllinae (Orthoptera: Tettigoniidae): 2n(♂)=35 and fn=35 the probable basic and ancestral karyotype of the family tettigoniidae - Ferreira, Amilton [UNESP]; Mesa, Alejo [UNESP] (Sociedade Entomológica do Brasil, 2010)
The karyotypes of five species of Brazilian Pseudophyllinae belonging to four tribes were here studied. The data available in the literature altogether with those obtained with species in here studied allowed us to infer that 2n(♂)=35 is the highest chromosome number found in the family Tettigoniidae and that it is present in species belonging to Pseudophyllinae, Zaprochilinae and in one species of Tettigoniinae. In spite of that all five species exhibit secondary karyotypes arisen surely by a mechanism of chromosomal rearrangement of centric fusion, tandem fusion and centric inversion types from those with 2n(♂)=35 and FN=35, they share some common traits. The X chromosome is submetacentric (FN=36), heteropicnotic during the first prophase, the largest of the set but its size is rather variable among the species and the sex chromosomal mechanism is of the XO( ♂ ), XX( ♀ ) type. The chromosomal rearrangements involved in the karyotype evolution of the Pseudophyllinae and its relationship with those of the family Tettigoniidae are discussed and we propose that the basic and the ancestral karyotype of the Tettigoniidae is formed by 2n(♂)=35, FN=35 and not by 2n(♂)=31, FN= 31, as usually accepted.
Keywords: Chromosomal rearrangement; fusion and centric inversion; evolution